Analysis of Palm Sugar Enterprises in Kekait Village as an Effort to Advance the Economic and Tourism Sectors - Rabiatun Adawiyah; Vina Maulida Rahmani; Dewi Rindiani; Fadhlina Shahira; Dida Ardani Immawansyah; Wira Alfarizi Surya; Fadlan Hakim; Yulanda Trisula Sidarta Yohanes (Future Tecno-Science Publisher, 2025)
The aren palm tree (Arenga pinnata) is a plant that is known to have a variety of uses because almost all parts of the tree can be utilized, ranging from the trunk, leaves, to the nira water produced from male flowers. The palm tree is utilized for various purposes, such as producing palm sugar, making traditional drinks, as well as raw materials for handicrafts and construction. In particular, the community mostly utilizes the nira water produced by the palm tree as an important raw material for making palm sugar. The nira water produced is utilized by a group of people in Kekait Village to produce palm sugar that has a very good quality with a distinctive natural sweet taste without any additional sweeteners. In Kekait village, there is an UMKM called PONEK Sugaren, which plays an important role in producing and developing traditional palm sugar products. The purpose of this palm sugar production is to utilize the abundant nira water as well as a form of community effort to advance the underdeveloped economy in Kekait village. But after this palm sugar product is ready to be marketed, there are obstacles in the form of marketing strategies that are less effective and have not been expanded. So it is necessary to improve the marketing strategy and the need to expand to market the product. The research method we use is a qualitative approach with observation, interview, and documentation methods, in the hope of getting more information and also relevant.